Multinational Union Activity in the Paper Industry - Northrup, Herbert; Rowan, Richard (Relations industrielles / Industrial Relations, 1979)
After considering the many attempts of cooperation among unions in multinational firms particularly the paper industry, the authors are not optimistic about results in the immediate future.